Studi Kasus: Analisis Kesulitan Guru dalam Merancang Modul Ajar Berdasarkan Hasil Visitasi - Sartika Sartika; Haidar Akmal Ghifari; Neng Wulan Anatasya (Lembaga Yasin AlSys, 2026)
The implementation of the Kurikulum Merdeka requires teachers to develop flexible, student-centered teaching modules that are aligned with the principles of differentiated instruction and diagnostic assessment. However, in practice, various challenges persist when teachers attempt to design teaching modules in a comprehensive and contextual manner. This study aimed to evaluate the challenges faced by teachers in designing Kurikulum Merdeka teaching modules based on school visit findings. A qualitative approach with a case study design was employed, with the subject being a fifth-grade teacher at a public elementary school in Sumedang Regency selected through purposive sampling. Data were collected through in-depth interviews, document analysis of the teaching modules, and review of visit notes, and were analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. The findings show that the teacher experienced difficulties in designing comprehensive diagnostic assessments, formulating learning objectives based on the ABCD principle, and implementing varied instructional methods suited to students’ needs. In addition, the teaching modules developed still resembled the Kurikulum 2013 format and had not fully reflected the characteristics of the Kurikulum Merdeka. Factors such as high workload, limited technological facilities, and insufficient time to optimally prepare instructional materials further exacerbated these obstacles. The study concludes that the success of teaching module design depends not only on teachers’ conceptual understanding of the Kurikulum Merdeka, but also on systemic support, resource availability, and ongoing mentoring. The implications highlight that strengthening technical assistance for teachers and institutional support is essential to improving the quality of instructional planning in the implementation of the Kurikulum Merdeka in elementary schools.